2015
DOI: 10.1097/psy.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Depression, Cognitive Impairment Without Dementia, and Dementia With Risk of Ischemic Stroke

Abstract: Objective To determine if depression, cognitive impairment without dementia (CIND), and/or dementia are each independently associated with risk of ischemic stroke and to identify characteristics that could modify these associations. Methods This retrospective-cohort study examined a population-based sample of 7,031 Americans > 50 years old participating in the Health and Retirement Study (HRS) (1998-2008) who consented to have their interviews linked to their Medicare claims. The 8-item Center for Epidemiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
2
16
0
3
Order By: Relevance
“…In particular, dementia ascertainment relied on brief cognitive tests instead of the clinical and neuropsychological evaluations used in previous studies (Terracciano et al, 2014; Wilson et al, 2007). However, the validity of these brief assessments of personality and cognitive status had been previously demonstrated (Clark et al, 2013; Crimmins et al, 2011; Davydow et al, 2015; Lachman et al, 1997; Luchetti et al, 2014; Saczynski et al, 2015; Stephan et al, 2016; Sutin et al, 2016), and the magnitude and direction of the associations observed in the HRS were consistent with results of studies that used more in-depth measures of personality and cognitive status (Duberstein et al, 2011; Johansson et al, 2014; Terracciano et al, 2014; Wilson et al, 2005; Wilson et al, 2007). Another limitation was the relatively short follow-up, but studies with longer time frame have found similar results (Johansson et al, 2014; Terracciano et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In particular, dementia ascertainment relied on brief cognitive tests instead of the clinical and neuropsychological evaluations used in previous studies (Terracciano et al, 2014; Wilson et al, 2007). However, the validity of these brief assessments of personality and cognitive status had been previously demonstrated (Clark et al, 2013; Crimmins et al, 2011; Davydow et al, 2015; Lachman et al, 1997; Luchetti et al, 2014; Saczynski et al, 2015; Stephan et al, 2016; Sutin et al, 2016), and the magnitude and direction of the associations observed in the HRS were consistent with results of studies that used more in-depth measures of personality and cognitive status (Duberstein et al, 2011; Johansson et al, 2014; Terracciano et al, 2014; Wilson et al, 2005; Wilson et al, 2007). Another limitation was the relatively short follow-up, but studies with longer time frame have found similar results (Johansson et al, 2014; Terracciano et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with other HRS-based studies (Clark et al, 2013; Crimmins et al, 2011; Davydow et al, 2015; Saczynski et al, 2015), we classified individual’s cognitive status based on the modified Telephone Interview for Cognitive Status (TICSm), which was administered at baseline and at every 2-year follow-up. The TICSm included measures of short-term memory, working memory, attention, and processing speed.…”
Section: Methodsmentioning
confidence: 99%
“…Os sinais clínicos associam-se à localização e extensão da lesão causada pelo AVC (Cumming et al, 2013 incapacidade funcional e cognitiva e, cerca de um terço desta população desenvolvem transtorno depressivo (Davydow et al, 2015).…”
Section: Figura 2 Mapa De Localização Da Província De Luandaunclassified
“…Transtorno depressivo e demência atuam individualmente como fatores de risco em potencial para a ocorrência de AVC (Davydow et al, 2015;Dong et al, 2012). Estudos sugerem que a associação entre depressão e risco para AVC é maior para indivíduos do sexo feminino Jackson CA, et.…”
Section: Figura 2 Mapa De Localização Da Província De Luandaunclassified
See 1 more Smart Citation